Experimental investigation of photocatalytic degradation and antioxidant activities of biosynthesized gold nanoparticles from royal poinciana tree leaves - L. Natrayan; M. Karthick; Chunchu Balarama Krishna; G. Velmurugan; M. Sai Chaithanya; Ramya Maranan; Wubishet Degife Mammo (Discover Applied Sciences)
Abstract In this current work, gold nanoparticles (AuNPs) that were biosynthesized from the leaves of the Royal Poinciana Tree (Delonix regia) were experimentally investigated for their photocatalytic decomposition and antioxidant properties. Using plant extracts as reducing and stabilizing agents, the synthesis of AuNPs was carried out sustainably. Advanced methods for assessing the dimension, structure, and crystallization of the resulting gold nanomaterials included transmission electron microscopy (TEM), Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), and UV–visible spectroscopy. The RP-AuNPs were mostly spherical, and the average particle size was 22.36 nm, according to the TEM images. The potential of the biosynthesized AuNPs photocatalytic activities to break down 4-nitrophenol (4-NP) pollutants when exposed to sunlight was assessed. The nanoparticles also showed good ultrarapid catalytic capacity for the 10-min, 0.337-min⁻1 rate of reactions and a consistent decrease in 4-nitrophenol to p-aminophenol in a solution of NaBH4. The pseudo-first-order kinetic model was used to describe the photodegradation process. These findings support the notion that royal poinciana is a promising bioresource for producing AuNPs with various uses. This research also tested the antioxidant power of RP-based AuNPs by scavenging DPPH radicals. Their IC50 value was 55.32 µg/ml using a sigmoidal curve-fitting model, which means they are excellent at eliminating free radicals.